Visible-light-active unsymmetrical squaraine dyes with 1 V of open-circuit voltage for dye-sensitized solar cells - Singh, Amrita; Kumar Singh, Ambarish; Dixit, Ruchi; Vanka, Kumar; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (ChemPhotoChem, 2023)
A series of alkyl-group-functionalized, aniline- and indoline-donor-based, unsymmetrical visible-light-active squaraine dyes, AM1-3, were designed and synthesized. Dye-sensitized solar cell (DSSC) devices were fabricated with both I-/I-3(-) and [Cu(tmby)(2)](+/2+) electrolytes. DSSC devices sensitized with the AM1 and AM2 dyes showed relatively high-power conversion efficiency of 7.44 % and 7.22 %, respectively with I-/I-3(-) in the absence of chenodeoxycholic acid (CDCA) than those of the AM3 dye (5.41 %). The [Cu(tmby)(2)](+/2+) electrolyte along with poly(3,4-ethylenedioxythiophene) (PEDOT) as cathode material showed excellent open-circuit potentials (V-OC) of 1030, 1025, and 1001 mV with the DSSC efficiency of 8.05 %, 7.96 %, and 5.84 %, respectively, for the AM1, AM2, and AM3 dyes in the absence of CDCA. Here, the AM1 dye exhibited the maximum DSSC efficiency of 8.05 % and V-OC of 1030 mV, which is the highest obtained efficiency and V-OC for the visible-light active zwitterionic unsymmetrical-squaraine dye with copper-based electrolyte.
Keywords: Cu electrolytes; dihedral angle; Dye-sensitized solar cells; open circuit voltage; squaraine dyes

Visible-light-active unsymmetrical squaraine dyes with pyridyl anchoring groups for dye-sensitized solar cells - Deshmukh, Shivdeep Suresh; Maibam, Ashakiran; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (Langmuir, 2023)
Visible-light-active alkyl group-wrapped unsymmetrical squaraine dyes SD1-SD3 were synthesized, featuring an indoline donor and pyridine and carboxylic acid anchoring groups. Their photophysical, electrochemical, and photovoltaic characteristics were examined by fabricating a dye-sensitized solar cell (DSSC) device. Both carboxylic acid and pyridine anchoring groups containing squaraine dyes SD3 and SD2 possess similar photophysical and electrochemical characteristics. However, their photovoltaic performances were completely different. The SD3 dye with the carboxylic acid anchoring group displayed a DSSC device efficiency of 7.20% (V-OC 0.81 V; J(SC) 12.29 mA/cm(2)) using iodolyte (I-/I-3(-)) electrolyte, compared to SD1 (V-OC 0.659 V; J(SC) 4.97 mA/cm(2); and eta - 2.34%) and SD2 (V-OC 0.629 V; J(SC) 1.68 mA/cm(2); and eta - 0.84%), which were featured with pyridyl anchoring groups. These results were attributed to dye loading on the Lewis and Br & oslash;nsted acidic sites of TiO2 and the importance of aggregated structures for photocurrent generation. In the incident photon-to-current efficiency (IPCE) analysis, SD1 dye-sensitized devices exhibited photocurrent generation from both monomeric and aggregated dyes on the TiO2 surface. In contrast, SD2 showed photocurrent generation solely from aggregated states. Despite the introduction of long alkyl chains to reduce dye aggregation and charge recombination, the results indicated preferential charge injection from only the aggregated SD2 dye on TiO2. Fluorescence-quenching experiments indicated an efficient charge transfer from the aggregated SD2 dye to TiO2 compared to that of the monomeric dye. Cosensitization, a method to enhance the light-harvesting efficiency and photocurrent generation in DSSCs, was explored by simultaneously cosensitizing pyridyl-based dyes (SD1 and SD2) with a blue-colored carboxylic acid-based squaraine dye SD4. IPCE analysis demonstrated that both SD1 and SD4 contributed to generating a photocurrent of 9.11 mA/cm(2). The sequential cosensitization of SD1 and SD4 with the coadsorbent CDCA showed the highest performance, with a V-OC of 0.663 V, a J(SC) of 11.43 mA/cm(2), and an efficiency (eta) of 5.20%.
Keywords: co-sensitization; Design; Emmision; Fluorescent Dyes; High-Efficiency; Organic Dye; Ring

Visible, far-red, and near-infrared active unsymmetrical squaraine dyes based on extended conjugation within the polymethine framework for dye-sensitized solar cells - Singh, Amrita; Singh, Ambarish Kumar; Dixit, Ruchi; Vanka, Kumar; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (ACS Applied Energy Materials, 2024)
Alkyl group wrapped visible, far-red, and NIR active unsymmetrical squaraine dyes with pi-extension in the polymethine framework-based AM4-AM7 have been designed, synthesized, and utilized as sensitizers for dye-sensitized solar cells. To extend the pi-conjugation within the polymethine framework, thiophene moieties have been incorporated between the donor and acceptor moieties. Absorption spectroscopic studies revealed that pi-extension with each -C & boxH;C- unit resulted similar to 100 nm of redshift in the charge transfer transition with the lambda(maximum) of 541, 643, 747, and 833 nm for AM4, AM5, AM6, and AM7 dyes, respectively, with the molar extinction coefficient of >10(5) M(-1)cm(-1). The pi-extended conjugation-based AM6 and AM7 dyes showed improved light-harvesting efficiency (LHE), where the AM7 dye showed an LHE of 386 nm at 60%. Electrochemical studies of AM dyes revealed that the HOMO energy level of the sensitizers has been modulated systematically. Further, pi-extension within the polymethine framework showed a dramatic effect on V-OC, J(SC), and device efficiency when move from visible active AM4 to far-red active to NIR active AM7 dyes. The DSSC efficiencies of 7.35, 5.18, 0.08, and 0.053% have been achieved with the I-/I-3(-) electrolyte (Z-50) for the AM4, AM5, AM6, and AM7 dyes, respectively. Further, AM4 dye has been cosensitized with AM5, AM6, and AM7 dyes, where AM4:AM5 (1:1) composition achieved the maximum efficiency of 8.12% with I-/I-3(-) electrolyte (Z-50) compared to the other cosensitization compositions.
Keywords: aggregation of dyes; DSSC device efficiency; light-harvesting efficiency; pi-extension; polymethine framework; squaraine dyes

Visible-light active π-extended unsymmetrical squaraine dyes for dye-sensitized solar cells: steric effects for controlling the aggregation of dyes - Jadhav, Avinash P.; Siby, Jesna; Pandya, Rinu; Vanka, Kumar; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (ACS Applied Energy Materials, 2025)
The dye-anchored TiO2 photoanode plays a vital role in the light harvesting and charge separation processes in dye-sensitized solar cells. Aggregation of dyes (H- and J-type) on the TiO2 surface is a facile process due to the presence of a periodical dye anchoring sites on the exposed facet of titania, and such self-assembled dye structures help broadening the absorption profile. However, photocurrent generation from such aggregated structure is a challenging task in dye-sensitized solar cell devices. Hence, controlling the dye aggregation on the TiO2 surface is an important aspect. Controlling the aggregation of dyes by which (i) an enhanced photocurrent generation (J SC) and (ii) enhanced V OC can be achieved by including the steric factors to the dye design principles, the steric factor in the sensitizer may help passivate the TiO2 surface to avoid the charge recombination process between electrons present in TiO2 and the oxidized electrolyte. On the other hand, extension of pi-conjugation in a sensitizer helps enhance the light absorption in the visible region besides modulating the HOMO and LUMO energy levels. Hence, synergizing both pi-extensions along with features that control the dye aggregation has been considered in designing visible active squaraine dyes. A thiophene pi-spacer was inserted in between a visible-light active unsymmetrical squaraine unit and a cyanoacetic acid acceptor unit to provide the AJ1 and AJ2 dyes. Though both the dye molecules possess a similar pi-framework, the AJ2 dye was functionalized with both in-plane and out-of-plane alkyl groups to decrease the aggregation of dyes on the TiO2 surface compared to AJ1. The AJ1 and AJ2 dyes absorbed at 560 nm with shoulder peaks appeared at 528 nm, which can be assigned to vibronic progression (1082 cm-1), and additional characteristic peaks of thiophene appeared at 392 nm with the molar extinction coefficient of 1.16-1.19 x 105 M-1 cm-1 in CH3CN. The LUMO and HOMO energy levels are well aligned with the conduction band of TiO2 and the redox potential of iodolyte (I-/I3 -) electrolyte with sufficient overpotentials for charge injection and dye regeneration processes, respectively. The highest DSSC device efficiency of 7.37% (J SC 14.44 mA/cm2, V OC 0.771 V, ff 67.1%) was achieved for the AJ2 dye with iodolyte (I-/I3 -) electrolyte in the presence of 2 equiv of optically transparent coadsorbent chenodeoxycholic acid (CDCA), which showed a good IPCE response in between 400 and 700 nm. Further, cosensitization of visible-light active AJ1, AJ2, and SQA10 dyes with a complementary far-red active SQS4 dyes showed the device efficiencies of 5.53% (AJ1:SQS4:CDCA), 7.14% (AJ2:SQS4:CDCA), and 7.18% (SQA10:SQS4:CDCA) with a good IPCE response in the 400-720 nm region.
Keywords: cosensitization; Dye aggregation; Dye-sensitized solar cells; pi-extended squaraine dye; visible-lightactivedyes